2017
DOI: 10.3892/or.2017.5363
|View full text |Cite
|
Sign up to set email alerts
|

In vitro long-term treatment with MAPK inhibitors induces melanoma cells with resistance plasticity to inhibitors while retaining sensitivity to CD8 T cells

Abstract: The development of BRAF V600 and MEK inhibitors constitutes a breakthrough in the treatment of patients with BRAF-mutated metastatic melanoma. However, although there is an increase in overall survival, these patients generally confront recurrence, and several resistance mechanisms have already been described. In the present study we describe a different resistance mechanism. After several weeks of long-term in vitro treatment of two different V600E BRAF-mutated melanoma cell lines with MARK inhibitors, PLX403… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…They demonstrated that vemurafenib-resistant melanoma cells become dependent on the drug for their continued proliferation. Likewise, Rowdo and co-authors reported that the melanoma cell subpopulation that survived prolonged treatment with vemurafenib showed quiescent/senescent cancer stem-cell-like characteristics and resistance plasticity, i.e., the cells can revert to the features of parental cells upon vemurafenib withdrawal [ 16 , 17 ]. Some authors considered melanoma cells resistant even if the difference between the IC 50 values of the parental and resistant cells was not found, due to other characteristics, such as increased ERK phosphorylation or a change in phenotype from epithelial to elongated and spindle-shaped [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that vemurafenib-resistant melanoma cells become dependent on the drug for their continued proliferation. Likewise, Rowdo and co-authors reported that the melanoma cell subpopulation that survived prolonged treatment with vemurafenib showed quiescent/senescent cancer stem-cell-like characteristics and resistance plasticity, i.e., the cells can revert to the features of parental cells upon vemurafenib withdrawal [ 16 , 17 ]. Some authors considered melanoma cells resistant even if the difference between the IC 50 values of the parental and resistant cells was not found, due to other characteristics, such as increased ERK phosphorylation or a change in phenotype from epithelial to elongated and spindle-shaped [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high heterogeneity level of melanoma, a single treatment modality cannot remove all cancer cells from the body. Following the appropriate treatment and surviving it, these cancer cells become resistant to the initial treatment modality and form a major subpopulation of recurrent melanomas [17]. Melanoma is a form of skin cancer closely related to the genetic changes that occur in the human body.…”
Section: Developmental Stages and Genetic Characteristics Of Melanomamentioning
confidence: 99%
“…SASP factors not only stimulate their own growth, invasion, and transformation processes and that of neighboring melanoma cells, but also induce immune suppressive cells (such as M2 polarized macrophages), thereby inhibiting immune clearance outcomes. Over time, these TIS melanoma cells reverse the aging process under the influence of epigenetic changes and accumulate mutation genes (such as activating mutations of NRAS and altered the expression of TP53 family isoforms) [67], and highly expressed multiple stemness-related genes, eventually leading to tumor recurrence and resistance behaviors [17,51,68]. Therefore, the elimination of TIS tumor cells has a positive effect on melanoma treatment outcomes.…”
Section: The Role Of Senescent Cells In Melanoma Therapymentioning
confidence: 99%